Description and comparison of postoperative functioning of patients with hip fracture 2018 and 2008 at the Örebro University Hospital - a comparative cross-sectional study - Amanda Hammer; Katarina Ljungberg; Tony Bohman; Åsa G Andersson (BMC Geriatrics, 2022)
Abstract Background Hip fractures are a global problem, and it will probably increase. Hip fractures impair health aspects which creates demands on postoperative care. This study describes and compares patients with hip fracture in 2008 and in 2018. An increased knowledge of this group could be a basis how to optimize aftercare and dimension rehabilitation. Methods Using a comparative cross-sectional study to describe and compare patients with hip fracture from 2018 and 2008 at Örebro University Hospital regarding age, sex, multimorbidity, fracture type, surgical materials, surgery within 24 hours, length of stay, postoperative walking ability, physical activity level and hand grip strength. Data was collected from 76 patients with hip fracture from 2018 and 78 patients from 2008. Outcome measures considering functioning were walking ability (Functional Ambulation Categories), physical activity level (Classification system of physical activity) and hand grip strength (Jamar hand dynamometer). Statistical analyses used were hypothesis tests and regressions analysis. Results No differences in age, sex, fracture type, proportion of surgery within 24 hours or length of stay between the cohorts. The cohort 2018 had more multimorbidity in number of diagnoses and ASA-classification preoperatively. In 2018 70% of the participants were dependent in walking ability (physical human support) compared to 43% 2008 (p = 0.007). Proportion of physically inactive was 9% in 2018 compared to 21% 2008 (p = 0.047). Hand grip strength was 5.1 kg better in 2018 (p = 0.011). Adjusted for age, sex, ASA-classification (American Society of Anaesthesiologists Classification System), surgical materials and number of days between surgery and testing the cohort of 2018 had a lower odds to have independent walking ability and higher odds to be physical active. Differences in hand grip strength decreased to 4.7 kg. Participants in 2018 suffered significantly more multimorbidity. Conclusions Study indicated differences in patients’ postoperative functioning between 2018 and 2008 with more impaired walking ability, more multimorbidity, higher proportion of physically active and better hand grip strength 2018. The results are important for future reasoning regarding care needs of patients with hip fracture.